Acute diffuse leukoencephalitis in HIV-1 infection. Issue 1 (January 1994) - Lüer, W; Gerhards, J; Poser, S; Weber, T; Felgenhauer, K
Abstract : The clinical, neuroradiological, and cerebrospinal fluid findings of a case with acute diffuse leukoencephalitis, a demyelinating disease associated with human immunodeficiency virus infection of the brain, is reported. The patient presented with acute tetraparesis as the primary manifestation of a previously symptom free HIV infection. Cerebrospinal fluid analysis showed enhanced inflammatory abnormalities with high concentrations of P24 antigen. MRI showed diffuse white matter hyper-intensities in both hemispheres. In the follow up over 22 months, the neurological deficits disappeared after antiretroviral treatment in good correlation with improvements in MRI as well as in inflammatory cerebrospinal fluid abnormalities.